2015
DOI: 10.3389/fmicb.2015.01389
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natural Organic Matter on Mercury Methylation by Desulfobulbus propionicus 1pr3

Abstract: Methylation of tracer and ambient mercury (200Hg and 202Hg, respectively) equilibrated with four different natural organic matter (NOM) isolates was investigated in vivo using the Hg-methylating sulfate-reducing bacterium Desulfobulbus propionicus 1pr3. Desulfobulbus cultures grown fermentatively with environmentally representative concentrations of dissolved NOM isolates, Hg[II], and HS− were assayed for absolute methylmercury (MeHg) concentration and conversion of Hg(II) to MeHg relative to total unfiltered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 113 publications
9
31
0
Order By: Relevance
“…Thus, this process needs to be further investigated in the field. Based on the Fe peak in the upper AOL, methylation may be driven by Fe‐reducing bacteria, which have been reported to prompt Hg desorption and methylation by using Fe oxides as electron acceptors (Hellal et al, ; Kerin et al, ; Schaefer et al, ; Si et al, ), whereas sulfate‐reducing bacteria (Benoit et al, ; King et al, ; Moreau et al, ; Schaefer et al, ) are likely to contribute significantly to Hg methylation in the lower part of the AOL, where HS − > 100 μM and increases with depth. However, they could also play a role in Hg methylation within aggregates settling from the SOL to the AOL (section 3.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this process needs to be further investigated in the field. Based on the Fe peak in the upper AOL, methylation may be driven by Fe‐reducing bacteria, which have been reported to prompt Hg desorption and methylation by using Fe oxides as electron acceptors (Hellal et al, ; Kerin et al, ; Schaefer et al, ; Si et al, ), whereas sulfate‐reducing bacteria (Benoit et al, ; King et al, ; Moreau et al, ; Schaefer et al, ) are likely to contribute significantly to Hg methylation in the lower part of the AOL, where HS − > 100 μM and increases with depth. However, they could also play a role in Hg methylation within aggregates settling from the SOL to the AOL (section 3.1).…”
Section: Resultsmentioning
confidence: 99%
“…In the deeper part of the AOL (σ θ > 17.04), Hg D and MeHg D concentrations increase to a second maximum (Figures 2, S1 and S2), which might be due to the enhanced solubility of Hg species in the presence of sulfides and DOM (Han, Lehman, et al, 2007;Mason et al, 1993;Ravichandran et al, 1998Ravichandran et al, , 1999Skyllberg, 2008;Slowey, 2010;Sunderland et al, 2006;Waples et al, 2005) and to net in situ methylation, which is favored by DOM (Graham et al, 2012;Moreau et al, 2015;Schaefer & Morel, 2009;Schaefer et al, 2011). It has been shown that in sulfidic systems, some DOM components (thiols, humic acids, and cysteine) delay or inhibit HgS (s) precipitation and favor its dissolution, leading to the formation of nanoparticles smaller than 0.2 μm (Deonarine & Hsu-Kim, 2009;Gerbig et al, 2011;Slowey, 2010): these nanoparticles can be methylated (Jonsson et al, 2012;Kucharzyk et al, 2015;Zhang, Kucharzyk, et al, 2014;Zhang et al, 2012).…”
Section: Observationsmentioning
confidence: 99%
“…The aromatic nature of DOM is a key predictor of Hg methylation (Graham et al., ; Moreau et al., ). Methyl‐Hg uptake may increase with DOM inputs of increasing aromaticity, sulfur content, and molecular weight, which are related to the greatest methylation of Hg by bacteria and subsequent formation of DOM–Hg complexes (Graham et al., ; Moreau et al., ). However, reductions in Hg uptake by bacteria and primary producers may occur if there is a shift to even larger and more refractory allochthonous DOM in lakes (Luengen, Fisher, & Bergamasch, ), either because the molecules are too large to pass through cell membranes (Ravichandran, ; Schartup, Ndu, Balcom, Mason, & Sunderland, ), or due to reduced DOM bioavailability and increased binding strength (French et al., ).…”
Section: Greater Risk Of Mercury Contaminationmentioning
confidence: 99%
“…The low growth efficiency of heterotrophic bacteria in oligotrophic lakes increases the number of C transfers through the microbial food web (Cotner & Biddanda, 2002) and, although speculative, may affect the fate of Hg. The aromatic nature of DOM is a key predictor of Hg methylation (Graham et al, 2013;Moreau et al, 2015). Methyl-Hg uptake may increase with DOM inputs of increasing aromaticity, sulfur content, and molecular weight, which are related to the greatest methylation of Hg by bacteria and subsequent formation of DOM-Hg complexes (Graham et al, 2013;Moreau et al, 2015).…”
Section: Greate R Risk Of Mercury Contaminationmentioning
confidence: 99%
“…Chloride concentrations in Cub Bath were higher than those of typical freshwaters (0.82 mM), and in combination with low pH, could have decreased net Hg methylation rates without impacting the viability of methylating microorganisms (77). Other factors that may influence Hg bioavailability include dissolved organic material (DOM) and thiol-DOM interactions (7981), and turbidity which likely limits photolytic Hg transformations.…”
Section: Discussionmentioning
confidence: 99%